Pengetahuan dan Perilaku Masyarakat dalam Pencegahan Demam Berdarah Dengue di Provinsi Jawa Barat dan Kalimantan Barat - Helper Sahat Parulian Manalu; Amrul Munif (ASPIRATOR - Journal of Vector-borne Disease Studies, 2016)
Dengue Hemorrhagic Fever (DHF) is a public health problem in tropical regions and caused the social and economic impacts. The rapid spread of dengue fever due to dengue virus easily infect humans and supported by the attitudes and knowledge about the lack of this disease prevention. The aim of this research is to determine the knowledge and habits of society to control the prevention of Dengue Hemorrhagic Fever in West Java and West Kalimantan. This study using a cross sectional design with a questionnaire as an instrument of research, conducted on 600 respondents in four City / County that has the most high endemicity related to the research problem, which is taken by simple random sampling. The results showed 92.8% of respondents had never heard of dengue fever, 77% of respondents have knowledge of dengue as infectious diseases, 81.5% of respondents know the modes of transmission of dengue by mosquito bites and about 63.7% of respondents take precautions through PSN (Breeding place control) plus Abate. This study revealed that the knowledge towards the prevention of dengue fever in the two provinces still classified as less positive, as well as people's habits which is still relatively poor in controlling the dengue